ENTREPRENEURIAL CHARACTER DEVELOPMENT STRATEGY FOR PRODUCTIVE AGE HOUSEWIVES - Avianti, Widiya; Affandi, Azhar; Djulius, Horas (IJBLE Scientific Publications Community Inc., 2023)
The creative economy industry can develop and progress with support from the Creative Economy Agency owned by the Government of Indonesia. The role of a woman is to take care of the family and manage household activities. When a woman owns or manages a business enterprise, the majority of locals seem to question her ability to strike a balance between work and family responsibilities. The significant function of micro, medium and small enterprises in Indonesia is owned and managed by women entrepreneurs. Respondents of productive age housewives in the DIY Upload community to illustrate and produce Human Resource Development Strategies for the formation of a strong Entrepreneurial Character in productive age housewives. The Strategy of Cooperation with External Parties and the Strategy for Increasing Management and Business Knowledge are strategies needed to improve weaknesses and seize opportunities for the formation of a Resilient Entrepreneurial Character.